Research on compliant configuration of hydraulic manipulator with passive following characteristic. Issue 14 (23rd October 2020) - Jiang, Lin; Ren, Lisheng; Pan, Xiaoyue; Zhu, Jianyang; Zhao, Hui
Abstract : To decrease the injury caused by an accidental collision between the hydraulic manipulator and human, a hydraulic rotating angle self‐servo compliant robot driver joint is designed. Based on this joint, a variable stiffness passive servo‐hydraulic rotary joint is improved. The passive follow‐up characteristics of the improved servo‐hydraulic rotary joint enable it to enter the low stiffness mode by itself when it encounters collisions beyond the force limit. Combining this characteristic, the research method of the hydraulic mechanical arm flexible configuration is proposed. Firstly, the joint motion mode is defined by the Euler angle, and a variety of configurations conforming to the motion characteristics of the manipulator are determined. Then, the virtual prototype and collision environment are built, and the dynamic characteristics of the end effector of the arm under high and low stiffness are measured. The results show that the flexible configurations with passive follow‐up characteristics can significantly suppress the collision force. Finally, the visual method is employed to solve, draw, and compare the workspace of the selected compliant configuration, to obtain the optimal compliant configuration with both flexibility and motion, which provides theoretical guidance for the subsequent design of the compliant manipulator.